Pembiasaan Sholat Dhuha Sebagai Upaya Pembentukan Karakter Siswa: Studi Kasus di SD Muhammadiyah Galagah Hulu - Abdus Syukur; Humaidi Humaidi; Rahim Firdaus; Ridha Munawwir (Madrasah: Jurnal Pendidikan Madrasah, 2025)
Dhuha prayer is made a routine at Muhammadiyah Galagah Hulu Elementary School as a means of instilling religious values and discipline in students. This study aims to analyze the daily practice of Dhuha prayer at SD Muhammadiyah Galagah Hulu, focusing on the reasons for its implementation, historical background, students’ character development, and the challenges faced. The research employed a qualitative descriptive method through in-depth interviews with one of the teachers. The findings reveal that the habituation of Dhuha prayer was initiated to build students’ religious character, enhance discipline, and foster a sense of order in daily life. The program was first implemented after the school drew inspiration from an institution in Samarinda that applied a full day school system. The most significant positive impact observed is the improvement in students’ discipline, particularly their habit of arriving earlier before the learning process begins. However, the main challenge is that some students still perceive Dhuha prayer merely as a routine without deeper spiritual understanding. Therefore, this study suggests the need for innovative learning methods, stronger spiritual motivation, and active teacher involvement to instill the values of Dhuha prayer more profoundly.